(untitled) (Medico Legal Update, 2021)
Background: Insulin-sensitizer treatment with metformin is widely used in polycystic ovary syndrome (PCOS). However, the treatment effectiveness shows individual differences in PCOS patients. Organic cation transporter (OCT1) have been reported to mediate metformin transport in the liver. Polymorphisms of OCT1 genes may affect the activity of metformin transport and further influence the treatment response of metformin in PCOS patients. Materials and Method: In this study, we investigated the association between the polymorphism of OCT1 and the treatment effectiveness of metformin in PCOS patients. The single nucleotide polymorphism (SNPs) of OCT1 – R61C analyzed in 222 PCOS and 106 control women. Fasting serum glucose (FSG), fasting serum insulin and HbA1c which represented metformin treatment response, were conducted at the start of treatment and after three-month treatment. Results: The results demonstrated that the polymorphisms of OCT1 was associated with the variability of metformin response, most patients with reference allele (wild type) and heterozygous alleles of OCT1 (R61C) showed statistically significant metabolic response to metformin, while patients with mutant alleles showed less or statistically not significant response. Conclusion: Genetic polymorphisms of OCT1 contributed to different metformin treatment responses, and further study is needed to establish personalized treatment programs using a pharmacogenomic algorithm approach in PCOS patients.